IMPLEMENTASI PENILAIAN AUTENTIK UNTUK MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR MATEMATIKA SISWA SMP - Tri Astuti Arigiyati (Jurnal Penelitian LPPM (Lembaga Penelitian dan Pengabdian kepada Masyarakat) IKIP PGRI MADIUN, 2016)
The purpose of this research was to determine the activity and mathematics achievement of grade 8 at Kartika’s Junior High School by implementing authentic assessment. This research is a Classroom Action Research (CAR). Observation and test techniques collected data. The observation was to know the students’ activity by analyzed percentage of items- indicators, while the mathematics achievement was analyzed by determining the average value and the percentage of classical completeness. The results showed that by implementing authentic assessment in mathematics could increase activity and students’ achievement. They were revealed by data from the pre-cycle, 1stcycle, and 2ndcycle. The average percentage of achievement indicators of the activity in the first cycle was 51.44% and then increased to78.85% in the second cycle. Classical completeness percentage increased from 50% in pre- cycle increased to 69.23% in the first cycle and increased to 76.92% in the second cycle. It is expected that teachers use authentic assessment systems in their learning process.